Giuseppe Mazzini's Young Europe and the birth of modern nationalism in the Slavic world - Procyk, Anna, 1937- (University of Toronto Press, 2019)
This book explores the influence of Young Europe - an international alliance founded by Giuseppe Mazzini in 1834 - on the Polish, Slovak, Czech, and Ukrainian intelligentsia in the first half of the nineteenth century.